Working Value in Local Knowledge of Akit Berancah Tribe, Bengkalis District - Indrawati, Indrawati; Nurhamlin, Nurhamlin; Rosaliza, Mita (Budapest International Research and Critics University, 2021)
Local knowledge of the Akit tribe community in utilizing nature has a trade-off between the nature of fulfilling the needs of life and the conditions of natural sustainability, the Akit Tribe of Berancah village utilizes mangrove forest as their livelihood as a supplier of Mangrove wood to Panglong Charcoal. Using qualitative-descriptive methods, this research involved 6 informants namely the Akit Tribe community and 4 key informants including Batin. Through interviews with research subjects in Berancah village, Bengkalis Regency, it shows that the local knowledge of the Akit Tribe community based on the value orientation concept has its own definitions according to local aspects. It has a relationship in the pattern of acting in the face of nature, therefore it is necessary to focus on local knowledge, especially in intrinsic values regarding to the work that is very closely related to the existence of mangrove forests, for their using of mangrove wood wisely brings the preservation of forests in coastal areas to be well maintained. Bengkalis Regency, it shows that the local knowledge of the Akit Tribe community based on the value orientation concept has its own definitions according to local aspects. It has a relationship in the pattern of acting in the face of nature, therefore it is necessary to focus on local knowledge, especially in intrinsic values regarding to the work that is very closely related to the existence of mangrove forests, for their using of mangrove wood wisely brings the preservation of forests in coastal areas to be well maintained. Bengkalis Regency, it shows that the local knowledge of the Akit Tribe community based on the value orientation concept has its own definitions according to local aspects. It has a relationship in the pattern of acting in the face of nature, therefore it is necessary to focus on local knowledge, especially in intrinsic values regarding to the work that is very closely related to the existence of mangrove forests, for their using of mangrove wood wisely brings the preservation of forests in coastal areas to be well maintained.